Steuerreformvorschläge in der Diskussion - Eine Mikrosimulationsanalyse der Aufkommens- und Verteilungswirkungen für Österreich - Eckerstorfer, Paul; Steiner, Viktor; Wakolbinger, Florian (Wirtschaft und Gesellschaft, 2014)
By using a microsimulation model, we analyze income-tax-reform proposals for Austria. The proposals include compensation for bracket creeping during the last years and a reduction of marginal tax rates, combined with a broader tax base. Moreover, they make the tax regime simpler. They are to be distinguished by different adjustments of family benefits, and they also differ in distributional effects and fiscal costs. On the basis of the first survey of household wealth in Austria, the "Household Finance and Consumption Survey" (HFCS), we show to what extent the fiscal costs of the income-tax-reform proposals could be financed by different wealth-tax regimes. Furthermore, we discuss the potentials of reducing government expenditure as an alternative to taxing wealth.